Hematological immune related adverse events after treatment with immune checkpoint inhibitors. (April 2021) - Kramer, Rafaela; Zaremba, Anne; Moreira, Alvaro; Ugurel, Selma; Johnson, Douglas B.; Hassel, Jessica C.; Salzmann, Martin; Gesierich, Anja; Weppler, Alison; Spain, Lavinia; Loquai, Carmen; Dudda, Milena; et al.
Abstract: Introduction: With the increasing use of checkpoint inhibitors, rare immune-related adverse events (irAE) are being identified. Haematological irAE (hem-irAE) are difficult to treat and have shown high mortality rates. In order to improve side-effect management for these potentially life-threatening events, we analysed frequency, severity and outcomes. Patients and methods: Patients who developed hem-irAE while being treated with immune checkpoint inhibitors (ICI) therapy were retrospectively identified from 18 international cancer centres. Results: In total, more than 7626 patients treated with ICI were screened, and 50 patients with hem-irAE identified. The calculated incidence amounts to 0.6% and median onset was 6 weeks after the ICI initiation (range 1–128 weeks). Thrombocytopenia and leucopaenia were the most frequent hem-irAE with 34% (17/50) and 34% (17/50), respectively, followed by anaemia 28% (14/50), hemophagocytic lymphohistiocytosis (4% (2/50)), aplastic anaemia (2% (1/50)), acquired haemophilia A (2% (1/50)) and coagulation deficiency (2% (1/50)). Simultaneous thrombocytopenia and neutropenia occurred in two patients, concurrent anaemia and thrombocytopenia in one patient. Other than cessation of ICI (in 60%) and corticosteroids (in 78%), treatment included second-line immunosuppression in 24% of cases. Events resolved in 78% (39/50), while 18% (9/50) had persistent changes, and 2% (1/50) had fatal outcomes (agranulocytosis). Conclusion: Hem-irAE can affect all haematopoietic blood cell lineages and may persist or even be fatal. Management may require immunosuppression beyond corticosteroids. Although these irAE are rare, treating physicians should be aware, monitor blood counts regularly and promptly act upon detection. Highlights: Haematological immune-related adverse events are rare and initially asymptomatic. Anaemia, thrombocytopenia and neutropenia comprised 1/3 of cases each. Regular blood count and prompt management are crucial as hem-irAE can be fatal. Management may require immunosuppression beyond corticosteroids.